Implementasi Kincir dalam Meningkatkan Produktivitas Ikan Nila di Pokdakan Minasari, Purwosari, Baturaden, Banyumas, Jawa Tengah - Purbomartono, Cahyono; Rusman, Ade; Bagis, Fatmah; Filardhi, Mohamad Noufal; Lenterani, Febiana (Jurnal Gema Ngabdi, 2025)
Tilapia (Oreochromis niloticus) is a freshwater fish that has high economic value so that it is widely cultivated by the community with a high stocking density without the addition of technological tools that maintain water quality. This causes water quality to decline, followed by a decrease in tilapia productivity, resulting in large losses. This problem is faced by many fish farmer groups (Pokdakan) in Indonesia including Pokdakan Mina Sari. The purpose of this service is to implement pinwheel technology in maintaining aquaculture water quality to optimize the productivity of tilapia cultivated by Pokdakan Mina Sari Purwosari Village, Baturraden, Banyumas, Central Java. The methods used in this service include socialization, training and mentoring. Socialization is carried out to introduce and convey the program to be carried out. Training was conducted to convey knowledge and skills including the application of mills, water quality management, handling of pests and diseases of tilapia, simple bookkeeping and marketing. Mentoring is carried out to assist partners in applying the technology delivered. The results of the service showed an increase in the enthusiasm and hard work of the farmer group members, an increase in tilapia productivity to 2-3 times from the original 2-3 quintals/pond to 6-9 quintals/pond, an increase in dissolved oxygen (DO) from 2-3 ppm to 5-6 ppm, an increase in fish weight/individual, an increase in fish feeding response, fish become more active, recording pond activities becomes more orderly, marketing has begun to serve retail buyers and there are fish processing activities. Therefore, this community service activity is very beneficial for fish farmers who are members of Mina Sari fish farmer group.